Search for an invisibly decaying Higgs boson in e+e- collisions at √s 183-189 GeV - Dova, María Teresa (2000)
A search for a Higgs boson decaying into invisible particles is performed using the data collected at LEP by the L3 experiment at centre-of-mass energies of 183 GeV and 189 GeV. The integrated luminosities are respectively 55.3 pb−1 and 176.4 pb−1. The observed candidates are consistent with the expectations from Standard Model processes. In the hypothesis that the production cross section of this Higgs boson equals the Standard Model one and the branching ratio into invisible particles is 100%, a lower mass limit of 89.2 GeV is set at 95% confidence level.